EFFICACY OF ULTRASOUND-GUIDED SAPHENOUS NERVE BLOCK USING BUPIVACAINE ALONE VERSUS BUPIVACAINE WITH TRIAMCINOLONE ACETONIDE IN OSTEOARTHRITIS KNEE PAIN - PIRKAD, ARJUN; TAXAK, SUHEELA; SINGH, DRPOONAM (International Journal of Current Pharmaceutical Research, 2025)
Objective: Knee osteoarthritis (OA) is a prevalent cause of chronic pain and functional impairment. Ultrasound-guided saphenous nerve block has emerged as a promising non-surgical treatment modality. This study evaluates the comparative efficacy of bupivacaine alone versus bupivacaine with triamcinolone acetonide in ultrasound-guided saphenous nerve block for OA knee pain. Methods: A prospective, randomized, double-blind study was conducted involving 80 patients aged 30–80 y with chronic OA knee pain (Grade II or III). Patients were allocated to two groups: Group T received 4 ml of 0.5% bupivacaine+40 mg triamcinolone acetonide; Group B received 4 ml of 0.5% bupivacaine alone. Both solutions were diluted to 10 ml with normal saline. Pain intensity (VAS), functional disability (WOMAC index), and patient satisfaction were assessed at baseline, 1 h, 1 w, 2 w, 1 mo, 3 mo, and 6 mo post-block. Results: Both groups showed significant reductions in VAS and WOMAC scores over time (p<0.05). However, Group T showed superior pain relief and functional improvement at all follow-up points (p<0.05). Grade II OA patients in both groups had better outcomes compared to Grade III. No significant procedural complications were noted. Conclusion: Ultrasound-guided saphenous nerve block using bupivacaine with triamcinolone acetonide provides prolonged and superior analgesia and functional improvement compared to bupivacaine alone in patients with OA knee. This technique is safe, effective, and minimally invasive, warranting consideration in non-surgical OA knee management.